Air Chemical Non-Equilibrium Effects on the Hypersonic Combustion Flow of RCS with Gaseous Ethylene Fuel (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, air chemical non-equilibrium effects on the shock-inducedcombustion flow are numerically investigated for a reaction control system (RCS) withgaseous ethylene fuel by solving multi-component Navier-Stokes (N-S) equations. Anintegrated numerical method is developed that considers two different chemical reactionmechanisms: the high temperature air chemical non-equilibrium reactions andethylene-oxygen combustion reactions. The method is independently validated bytwo types of reacting flow: the hypersonic air chemical non-equilibrium flow over asphere and supersonic ethylene-oxygen combustion flow for a dual combustion chamber.Furthermore, the mixed reacting flow over a blunt cone with a transverse multi-componentgaseous jet is analyzed in detail. Numerical results indicate that air chemicalnon-equilibrium effects could lead to a reduction of the shock detachment distance,a decrease of the temperature behind the shock wave and a reduction of the combustionproducts.